Preparation of a Norm or Measure for Evaluating the Artistic Works in the Field of Sculpting for Students of College of Fine Arts of Salahaddin University - Karwan Rashid Hassan; Jawad Nemat Hussein (QALAAI ZANIST JOURNAL, 2024)
The existence of an academic requirement is very important in the evaluation of works of art, which ultimately lead to the promotion and involvement in the enhancement of the value of works of art. In order to make this process scientific, the researcher conducted research entitled (Prepare a criterion for evaluating expressive artworks on the subject of tangible sculpture for students of Salahaddin University / College of Fine Arts / Department of Fine Arts / Sculpture Branch / Fourth Stage). Based on the nature and purpose of the subject, the researcher conducted a descriptive search to develop a scale. It consists of four chapters: Chapter One: Contains the general framework of the research consisting of (problems, aims, limits) of the research and defining terms. The research problem is contained in this question: What are the basic criteria used in the criteria for evaluating expressive artworks in the field of concrete sculpture for students of the sculpture branch in the department of fine arts at college of fine arts? Chapter Two: The theoretical framework of research comprises and consists of two research studies with a presentation of previous research. The First Topic: Introduces measuring and evaluating. The Second Topic: A summary of the expressive movement. Chapter Three: Research procedures include the following Research method: The study was done using a descriptive method. Research sample: Seven sculptures done in an expressive manner. Research tools: Using the scale prepared by the researcher that consisted of (7) units and (20) paragraphs, after deducing the sincerity of the appearance by obtaining the opinion of elite experts in the field of sculpture and painting. The stability of the model was determined by re-evaluation of a sample of artwork by three experienced academic raters using the person statistical model. Chapter Four: Is made up of research findings, recommendation, and further recommendations. The final sample of the prepared standards was obtained from the study, it consists of (7) units, (20) paragraphs and (5) levels.